Vascular Access Related Infections Among Hemodialysis Patients In Tritiary Care Centre, Tamilnadu - ANANDHI LAKSHMANAN; RADHA MADHAVAN; PADMANAABAN (International Journal of Pharma and Bio Sciences, 2012)
Background: Vascular access related infections (VARI) are important causes of increased mortality, morbidity and cost of therapy among hemodialysis patients. Prevention of VARI requires the identification of predisposing risk factors. SAMPLING AND METHODOLOGY: As per CDC guidelines, suspicion was made, and from them all possible samples were taken, 5-10 ml of blood both from Catheter and peripheral from patients with fever/rigors/hypotension. Exit-site swab when purulent discharge and Catheter tips (Suspected and non-suspected) removed aseptically for which semi-quantitative catheter tip culture by Maki’s Roll plate method was done. This was followed by collection the samples inoculated into appropriate culture media plates and it was identified by its colony morphology and relevant biochemical reactions. RESULTS: Out of 156, 61 were catheterized patients and 95 were AVF. Of which 28 were suspected based on CDC guidelines i.e., 21 from catheterized and 7 from patients with AVF. Based on nature of catheter used, the highest risk of infection was found in permanent catheters than temporary catheters. Based on anatomical catheter site, FVC was found to be at more risk of infection in our study with 60%.Polymicrobial growth was also seen in patient with FVC. Based on antibiogram, S.aureus, 2 out of 6 showed resistance to oxacillin and Enterococci, 1 out of 3 showed resistances to vancomycin and the only E.coli was found to be MDR type. DISCUSSION: Vascular access related infections includes risk factors such as duration of catheterization maintenance which is more than the recommended days, increased preference of catheters than AVF due to late diagnosis of CKD and late referral to nephrologists and vascular surgeons for timely construction of AVF, anatomical site used. Also organisms in our study are mostly skin micro-organism found on patients and hands of health care workers, which indicates poor hand hygiene and inadequate or improper use of sterile technique. Our study’s antibiogram result indicates the liberal usage of antibiotics.